in vitro Antidiabetic, Antioxidant and Cytotoxic Activities of Syzygium cumini Fractions from Leaves Ethanol Extract - Nina Artanti; Faiza Maryani; Rizna Triana Dewi; Sri Handayani; Indah Dwiatmi Dewijanti; Lia Meilawati; Euis Filaila; Linar Zalinar Udin (Indonesian Society for Cancer Chemoprevention, 2019)
Ethanol extract of Syzygium cumini (jamblang) leaves reveal its significant α-glucosidase inhibitory activity which perform the potential activity of this plant extract as antidiabetic agent. However, other bioactivities of this plant extract have been reported. The aim of current study was to evaluate the comparison of in vitro antidiabetic, antioxidant and cytotoxic activity of S. cumini fractions. The S. cumini leaves ethanol extract was fractionated by using column chromatography with n-hexane, ethyl acetate and methanol as eluents. Seven fractions were obtained from column chromatography (F1-7). The results showed that the best antidiabetic activity was found in F5 (93% α-glucosidase inhibitory activity), the best antioxidant activity was found in F4 (83% inhibition of DPPH free radical) and the best cytotoxic activity was found in F2 (69% growth inhibition of T47D breast cancer cell line). Therefore besides in vitro antidiabetic activity, fractions of S. cumini leaves ethanol extract also showed antioxidant and cytotoxic activities. Since the results showed that the most active fractions for antidiabetic, antioxidant and cytotoxicity were differed, it could be possible to isolate the different potential active compounds for each activity.Keywords : Syzygium cumini, α-glucosidase inhibitor, DPPH, cytotoxicity